The Role of Long Noncoding RNAs in Central Nervous System and Neurodegenerative Diseases - Wei, Chang-Wei; Luo, Ting; Zou, Shan-Shan; Wu, An-Shi (Frontiers in Behavioral Neuroscience, 2018)
Long non-coding RNAs (lncRNAs) refer to a group of non-coding RNAs (ncRNAs) that has a transcript of more than 200 nt in length in eukaryotic cells. LncRNAs can regulate gene expression by epigenetic means, as well as their transcriptional and post-transcriptional levels. In-depth studies on the function of lncRNAs in the central nervous system and its mechanism will help deepen our understanding of the development, function and diseases of the nervous system; and provide new ideas for the design and development of some therapeutic drugs. This review makes a comprehensive analysis of the relevant mechanism of lncRNAs in the central nervous system, in order to provide a new idea for the establishment of the neural control network and the prevention and treatment of neurodegenerative diseases. In recent years, with the extensive application of second generation sequencing technology, the mystery of lncRNAs has been gradually disclosed. The accumulation of research data reveals that lncRNAs are involved in the regulation of cell differentiation and individual development, as well as other important life processes at multiple levels, which are closely associated to many critical diseases of mankind. This review sums up the relevant information of lncRNAs and its role in the central nervous system, in order to provide a new idea for the establishment of the neural control network and the prevention and treatment of neurodegenerative diseases.